Design patterns: Elements of Reusable Object-Oriented Software - Erich Gamma...[et al.] (Addison-Wesley, 1995)
Four software designers present a catalog of simple and succinct solutions to commonly occurring design problems, using Smalltalk and C++ in example code. These 23 patterns allow designers to create more flexible, elegant, and ultimately reusable designs without having to rediscover the design solutions themselves. The authors begin by describing what patterns are and how they can help you design object-oriented software. They go on to systematically name, explain, evaluate, and catalog recurring designs in object-oriented systems.--From publisher description.